Why Software Engineering Courses Should Include Ethics Coverage. - Narayanan, Arvind; Vallor, Shannon (Communications of the ACM, 2014)
The authors offer opinions on computer software engineering education. It is argued that the ethics curricula mandated for engineering higher education in other fields such as civil and electrical engineering should be extended to the teaching of software engineering and development due to the ubiquity and importance of computer software in contemporary life.